Fatigue in type 1 diabetes: A systematic review of Observational studies. (January 2017) - Jensen, Øystein; Bernklev, Tomm; Jelsness-Jørgensen, Lars-Petter
Highlights: Out of 4258 papers identified, 10 papers addressed fatigue/vitality in type 1 diabetes. Three studies assessed fatigue as the primary endpoint. Only one of the included studies were judged to be of high methodological quality. There is generally a lack of well-designed studies that investigate the influence of socio-demographic as well as clinical factors in type 1 diabetes. Abstract: Aim: To systematically review the literature on fatigue in people with type 1 diabetes. Methods: In the period from April to June 2015 and with an updated search in May 2016, eight electronic databases as well as the grey literature were searched. Studies of all types of design were included if they reported data on fatigue in adult people with type 1 diabetes. All studies were assessed for quality. Results: Out of 4259 references (including grey literature), 10 papers were reviewed in full. Three of these papers investigated fatigue as the primary endpoint, and one was assessed to be high quality. Two papers provided a definition of fatigue. Prevalence estimates ranged from 23 to 40%, dependent on the cut-off used. Six different questionnaires were used to measure fatigue/vitality and these were only validated to a limited extent in a diabetes population. Several demographic, personal and clinical factors were associated with fatigue, but the results were conflicting. Conclusions: Few studies have been published that investigate fatigue in type 1 diabetes and there is a large variability in findings due to different measurement methods and factors investigated. There is still an unmet need to understand what contributes to fatigue in these patients through rigorous research.